Effect of surface defects on structure failure: A two-scale approach - Brancherie, Delphine; Dambrine, Marc; Vial, Grégory; Villon, Pierre (European Journal of Computational Mechanics, 2008)
This work aims to take into account the influence of boundary defects on the behaviour till rupture of structures without any fine geometrical description of the domain. This is achieved by appealing to two approaches: an asymptotic analysis of Navier equations and strong discontinuity models. We present in this work a strategy to couple the two approaches in order to provide the analysis till rupture of the structure behavior. The approach is validated on an academic example.